2022
DOI: 10.1021/acs.jpclett.2c01534
|View full text |Cite
|
Sign up to set email alerts
|

Particle-in-Molybdenum Disulfide-Coated Cavity Structure with a Raman Internal Standard for Sensitive Raman Detection of Water Contaminants from Ions to <300 nm Nanoplastics

Abstract: To develop a universal and precise detection strategy that can be applied to water contaminants of various sizes, we designed a particle-in-MoS 2 coated cavity structure of AAO/MoS 2 /Ag with a Raman internal standard. This modified particle-in-cavity structure not only successfully integrates both "surface hot spots" and "volume hot spots" via dressing and manipulating the cascaded optical-field mode inside the cavity but also introduces the chemical enhancement and internal standard attribute of MoS 2 . Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…It has been demonstrated that such AAO dimensions help achieve better light utilization in the nearinfrared region. [49,50] The physical images of the large-scale 3D CIC SERS substrate preparation process are shown in Figure 3A-D. The CIC SERS substrates were prepared by transferring monolayers of Au TCNCs on the surface of 2 cm long AAO templates (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that such AAO dimensions help achieve better light utilization in the nearinfrared region. [49,50] The physical images of the large-scale 3D CIC SERS substrate preparation process are shown in Figure 3A-D. The CIC SERS substrates were prepared by transferring monolayers of Au TCNCs on the surface of 2 cm long AAO templates (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…This study provides new ideas and tools for the detection of environmental nanoplastics. Li et al 110 also designed a SERS substrate similar to the Klarite structure, a 3D material based on a modified particle-in-cavity (PIC) structure, consisting of AAO conical pores, MoS 2 layers and Ag NPs, which has been used to characterize nanoplastics (<300 nm). The PIC structure integrates "surface hotspots" and "volume hotspots" and introduces the internal standard property of MoS 2 , its curved inverted cone facilitates the capture of nanoplastics and simultaneously achieves high SERS enhanced detection.…”
Section: Metal Nanostructure Arrays Sers Substratesmentioning
confidence: 99%
“…The enhancement region is limited to the nearby surface of the structure (∼1–10 nm), which limits the detection of particles of various sizes. , Nanoarray substrates with PIC structures combine a “volume hot spot” (inside the cavity) and a “surface hot spot” (on the surface of the nanostructure), extending the effective area of the conventional local electric field in SERS structures and facilitating the detection of particulate targets (Table ). Substrate stability and interference resistance. Impurities carried by SERS substrates are mainly introduced during the synthesis.…”
Section: Strategies and Advances In Sers Detection Of Nanoplasticsmentioning
confidence: 99%
“…The high SERS sensitivity and uniformity are due to the efficient enhancement ability of porous 3D PIC structure and highly ordered periodic array ( Liu, et al, 2022 ; Wang, et al, 2022 ). As illustrated in Figure 1E , Li et al (2022) designed a quasi-periodic PIC Raman substrate structure based on silver nanoparticles and anodic alumina templates to achieve sensitive detection at the single-molecule level and further improved the detection accuracy by introducing molybdenum disulfide as an internal standard. With the advantages of local hot spots, spatial hot spots and high adsorption properties of PIC structure intrinsic, the AAO/MoS 2 /Ag 3D structure achieved sensitive detection of multi-size pollutants including heavy metal ions, small molecule pollutants, and nano plastics in the water.…”
Section: Wearable Surface-enhanced Raman Scattering Sensors:design An...mentioning
confidence: 99%